Technique for querying over an encrypted database - Dheyaa Mohammed, Sahab; Abdul Monem S. Rahma, Prof Dr. (International Journal of Engineering & Technology, 2018)
The increase in the amount of data in encrypted databases has caused problems in data processing and retrieval. In conventional method, difficulties in querying an encrypted database are experienced because it is time consuming and requires large computations when designing encryption algorithms or creating indexing tables that expose non-authorized disclosure. In this study, we proposed a new technique for querying encrypted databases. This technique allows legitimate users to immediately query without decrypting all the encryption records. In this method, index fields were created by using the hash function, and new approaches of encoding and hiding data information were used. Thus, the query can be used without encryptions. Hence, the index values will not be exposed to speculation by outside attackers when the index table has been detected. The proposed technique could provide high data security and consume lesser time when retrieving records compared with traditional methods.Â